Electrostatic transparency of graphene oxide sheets. (May 2015) - Giusca, Cristina E.; Perrozzi, Francesco; Melios, Christos; Ottaviano, Luca; Treossi, Emanuele; Palermo, Vincenzo; Kazakova, Olga
Abstract: The interaction of graphene oxide of varying reduction degrees with dielectric and metallic surfaces is probed in this study, in order to assess the influence that the supporting substrate has on the electronic properties of as-produced graphene oxide and its reduced form. Lateral inhomogeneities in the distribution of substrate trapped charged impurities are found to affect the electronic properties of reduced graphene oxide, giving rise to significant in-plane variations of the local electrostatic potential on reduced one-layer sheets supported on dielectric substrates. On the contrary, no such surface potential fluctuations are identified on as-produced graphene oxide sheets, or on graphene oxide layers deposited on a metallic substrate. Thicker, two-layer reduced graphene oxide sheets show effective screening of the electrostatic effects caused by charge impurities trapped in the substrate. The current study provides a useful account of the limitations that device performance could face when attempting to tune the electronic structure of graphene oxide via functionalization, highlighting the role of substrate-related disorder affecting the behaviour of nanodevices. The role of the substrate is particularly important for applications where electronic properties of graphene oxide are especially targeted, such as transparent conducting films, sensors and electrochemical devices.